The Effect of Transformational Leadership on Organizational Commitment and Work Performance - Abu Muna Almaududi Ausat; Suherlan Suherlan; Tepi Peirisal; Zaenal Hirawan (Universitas Gadjah Mada, 2022)
Introduction/Main Objectives: Organizations must be responsive in an increasingly complicated and competitive business environment. Background Problems: To stay relevant, the leader's role must be maximized in cultivating and promoting the people resources they have. This is still a problem of leadership style applied in a business organization. Novelty: The transformational leadership style is the solution to a company's uneasiness in the face of a more dynamic and disruptive business environment, particularly for SMEs that are still learning how to execute the optimum leadership style.Research Methods: A quantitative technique based on variance Structural Equation Modeling (SEM) and Partial Least Squares (PLs) was used to acquire a better understanding of the relationship between variables. An online questionnaire was used to collect responses from SMEs employees in the food and beverage sector in Karawang Regency, Indonesia. Finding/Results: Transformational leadership has a good and significant impact on organizational commitment and work performance, according to the findings. Similarly, the commitment organizational to work performance. Organizational commitment, on the other hand, does not appear to be a significant mediating variable between transformational leadership and work performance. Conclusion: Although transformational leadership can have beneficial effects on employees like commitment and intimacy, it's important to remember that during the present Covid-19 pandemic, employees require a decent income from their work